Why Trust Matters - Ho, Benjamin (Tantor Media, Inc., 2021)
Have economists neglected trust? The economy is fundamentally a network of relationships built on mutual expectations. More than that, trust is the glue that holds civilization together. Every time we interact with another person-to make a purchase, work on a project, or share a living space-we rely on trust. Institutions and relationships function because people place confidence in them. Benjamin Ho reveals the surprising importance of trust to how we understand our day-to-day economic lives. Starting with the earliest societies and proceeding through the evolution of the modern economy, he explores its role across an astonishing range of institutions and practices. From contracts and banking to blockchain and the sharing economy to health care and climate change, Ho shows how trust shapes the workings of the world. He provides an accessible account of how economists have applied the mathematical tools of game theory and the experimental methods of behavioral economics to bring rigor to understanding trust. Bringing together insights from decades of research in an approachable format, Why Trust Matters shows how a concept that we rarely associate with the discipline of economics is central to the social systems that govern our lives.